Empowering High School Graduates: Soft Skills and Financial Report Training for Entrepreneurship and Workforce Success - Lailatun Nafisa (Indonesian Journal of Cultural and Community Development, 2023)
This scientific article presents a study aimed at addressing unemployment and fostering entrepreneurship by emphasizing the significance of soft skills in the business world. The research focuses on providing high school graduates with training in financial report preparation, aiming to augment their knowledge and insights in this domain. The implementation involves three stages: material delivery, practical exercises in financial reporting, and an evaluation process. The results demonstrate a remarkable enthusiasm among students participating in the training, as it not only enhances their understanding of financial reporting but also provides valuable insights beyond conventional education. This initiative can potentially empower graduates to navigate the world of work and entrepreneurship successfully. Highlight: Soft skills: Crucial for Entrepreneurship, Emphasizing the significance of soft skills in the entrepreneurial world and its impact on business development. Financial Report Training for Graduates, Highlighting the importance of providing high school graduates with knowledge and insights in financial reporting. Empowering the Workforce and Reducing Unemployment, Showcasing the role of education and government in tackling unemployment through enhanced soft skills and entrepreneurship training. Keywords: Soft skills, entrepreneurship, financial reports, high school graduates, training.